2023
DOI: 10.3389/fpls.2023.1109460
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics reveals the response of hydroprimed maize to mitigate the impact of soil salinization

Abstract: Soil salinization is a major environmental stressor hindering global crop production. Hydropriming has emerged as a promising approach to reduce salt stress and enhance crop yields on salinized land. However, a better mechanisitic understanding is required to improve salt stress tolerance. We used a biochemical and metabolomics approach to study the effect of salt stress of hydroprimed maize to identify the types and variation of differentially accumulated metabolites. Here we show that hydropriming significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 92 publications
2
0
0
Order By: Relevance
“…These results showed that the flavonoid biosynthesis pathway is important for mulberry seed germination under salt stress. Our results are consistent with previous studies reporting that flavones and flavonols accumulate in plants exposed to salt stress and that they enhance plant salinity tolerance by scavenging ROS [ 49 , 70 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results showed that the flavonoid biosynthesis pathway is important for mulberry seed germination under salt stress. Our results are consistent with previous studies reporting that flavones and flavonols accumulate in plants exposed to salt stress and that they enhance plant salinity tolerance by scavenging ROS [ 49 , 70 ].…”
Section: Discussionsupporting
confidence: 93%
“…Quercetin-3-O-glucoside has been shown to have high antioxidant activity, and moderate salinity induces the synthesis of quercetin-3-O-glucoside [ 48 ]. In addition, maize plants exhibited a significant increase in relevant metabolites, including quercetin 3-O-glucoside, kaempferol 3-O glucoside, and quercetin 3-methyl ether, under salt stress [ 49 ], which is similar to the results of this study. Taxifolin (dihydroquercetin) and its derivatives are flavonoids with important medicinal value that are widely distributed in plants and play important roles in the defense against biotic and abiotic stresses [ 50 , 51 ].…”
Section: Discussionsupporting
confidence: 85%